2000
DOI: 10.1007/s002849910034
|View full text |Cite
|
Sign up to set email alerts
|

Mcchs1 , a Member of a Chitin Synthase Gene Family in Mucor circinelloides , Is Differentially Expressed During Dimorphism

Abstract: A complete chitin synthase gene and one chitin synthase gene fragment of the zygomycete Mucor circinelloides have been cloned and analyzed. Both genes encode zymogenic Class II chitin synthases. Hybridization analysis showed that there must exist at least another Class II chitin synthase gene in M. circinelloides highly homologous to the cloned Mcchs1 and Mcchs2. The expression of these genes during the dimorphic growing stages was analyzed. Northern hybridizations showed that Mcchs1 transcript accumulates onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This suggests that it is possible that the presence of four pkaR genes is due to multiple rounds of whole-genome duplications, duplication of segments smaller than the entire genome, or duplications in individual genes. Although wholegenome duplication in the Zygomycetes phylogenetic branch is not supported yet by whole-genome analyses, gene duplication is a recurrent theme in Zygomycetes biology, and many examples have been published (16,18,39). Moreover, a comparative study of 34 complete fungal genome sequences, representing a broad diversity of Ascomycetes and Basidiomycetes species, and the zygomycete R. oryzae, showed that the multiplicity of isoforms for one protein varies greatly between fungal species, but the zygomycete R. oryzae possesses by far the highest number of duplication clusters of all of the fungi analyzed (9).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that it is possible that the presence of four pkaR genes is due to multiple rounds of whole-genome duplications, duplication of segments smaller than the entire genome, or duplications in individual genes. Although wholegenome duplication in the Zygomycetes phylogenetic branch is not supported yet by whole-genome analyses, gene duplication is a recurrent theme in Zygomycetes biology, and many examples have been published (16,18,39). Moreover, a comparative study of 34 complete fungal genome sequences, representing a broad diversity of Ascomycetes and Basidiomycetes species, and the zygomycete R. oryzae, showed that the multiplicity of isoforms for one protein varies greatly between fungal species, but the zygomycete R. oryzae possesses by far the highest number of duplication clusters of all of the fungi analyzed (9).…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of CHS genes has been shown to occur at the transcriptional and post-transcriptional levels. Transcriptional regulation was reported to take place during the dimorphic transition of Candida albicans [4], Mucor circinelloides [13] and Paracoccidioides brasiliensis [17], where in general mycelial genes were up-regulated. In the present study, we observed slightly higher transcript levels in mycelium, the exception being CHS4.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into consideration the importance of chitin and b-glucans in the construction of the cell wall, and the scant information on the level of regulation of the genes encoding their synthases [4,12,13,18,25] we have proceeded to analyze the transcriptional regulation of the genes encoding chitin and b-1,3-glucan synthases in U. maydis at different developmental stages, under some stress conditions, and during the invasion of its host. This Basidiomycota fungus is a specific pathogen of maize that requires its host to complete the sexual life cycle [for reviews see [5], [11], [22], [26]].…”
Section: Introductionmentioning
confidence: 99%
“…In other cases regulation occurs during cell differentiation, such as it occurs specifically with CaChs2 mRNA whose levels increase during the dimorphic transition of C. albicans [68]. Also during dimorphism of U. maydis, levels of transcripts of different CHS genes become elevated [69,70], and transcript from CHS1, but not other CHS genes accumulates in the mycelial, but not in the yeast forms of Mucor circinelloides [71]. Transcripts from P. brasiliensis CHS genes were detected in both yeastlike (Y) and mycelial (M) cultures where all exhibited similar patterns of expression during the M to Y transition, with a preferential expression in the M form.…”
Section: Multigenic Control Of Chitin Synthases In Fungimentioning
confidence: 96%